2016
DOI: 10.1111/jir.12350
|View full text |Cite
|
Sign up to set email alerts
|

The effect of slow‐paced breathing on stress management in adolescents with intellectual disability

Abstract: The slow-paced breathing task enhanced stress management to a greater extent than did listening to an audiobook. Slow-paced breathing seems to be an easy to learn stress management technique that appears as an effective auxiliary method of lowering stress in adolescents with intellectual disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 37 publications
1
47
0
2
Order By: Relevance
“…For example, it would be important to know what to do when the vagal tank is depleted. A fix of self-regulation failure could be realized for example with a mindfulness training ( Brewer et al, 2009 ; Libby et al, 2012 ) or with slow paced breathing ( Wells et al, 2012 ; Laborde et al, 2017a ), which would contribute to increasing cardiac vagal control. We would like to conclude with the words of Kurt Lewin: “There is nothing as practical as a good theory” ( Lewin, 1952 , p. 346), and we hope that the heuristic visualization offered by the vagal tank theory may help people to become aware on how to take action on their self-regulation abilities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it would be important to know what to do when the vagal tank is depleted. A fix of self-regulation failure could be realized for example with a mindfulness training ( Brewer et al, 2009 ; Libby et al, 2012 ) or with slow paced breathing ( Wells et al, 2012 ; Laborde et al, 2017a ), which would contribute to increasing cardiac vagal control. We would like to conclude with the words of Kurt Lewin: “There is nothing as practical as a good theory” ( Lewin, 1952 , p. 346), and we hope that the heuristic visualization offered by the vagal tank theory may help people to become aware on how to take action on their self-regulation abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory rate is one respiratory parameter that is both modified by affective state (Kreibig, 2010) and may influence it (e.g., Van Diest et al, 2014). Because of that, volitional slow breathing is widely used as an affect regulation tool (e.g., Chen, Huang, Chien, & Cheng, 2016;Laborde, Allen, Göhring, & Dosseville, 2016;Van Dixhoorn, 2007). In recent years, breathing around a frequency of 0.1 Hz (six breaths per minute) has been of particular interest in both basic and applied research because this frequency exerts a unique influence on the amplitude of cardiovascular oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…Biomarkers can be used to show whether a new or adapted treatment acts through/upon an assumed mechanism, thus providing proof-of-principle before embarking on full-scale trials. Such approaches are rarely used in ID research, but their usefulness is demonstrated by a study of slow-paced breathing, a simple but potentially effective stress-management strategy that often forms part of interventions for stress and anxiety (Laborde et al 2016 ). These authors measured cardiac efferent vagal tone (through heart rate variability) to show that this technique can potentially reduce stress in young individuals with intellectual disabilities.…”
mentioning
confidence: 99%